Variance estimation of changes in repeated surveys and its application to the Swiss survey of value added - Qualité, Lionel; Tillé, Yves (My University, 2008)
We propose a method for estimating the variance of estimators of changes over time, a method that takes account of all the components of these estimators: the sampling design, treatment of non-response, treatment of large companies, correlation of non-response from one wave to another, the effect of using a panel, robustification, and calibration using a ratio estimator. This method, which serves to determine the confidence intervals of changes over time, is then applied to the Swiss survey of value added.
Keywords: Covariance; Stratified sampling; Panel